Revitalisasi Lahan Bekas Tambang sebagai Langkah Rehabilitasi Bencana: Sebuah Tinjauan Konseptual - Bimantara, M. Aji; Rahmat, Hayatul Khairul; Hidayat, Marlina (Trends in Applied Sciences, Social Science, and Education, 2024)
Indonesia, as a country with abundant natural resources, is a strategic location for mining activities. However, mining activities that are not managed properly cause significant environmental impacts, such as land damage, loss of vegetation and soil pollution. To overcome this problem, reclamation and revitalization are important solutions in restoring and reusing ex-mining land. Reclamation aims to repair, manage and improve the quality of the environment so that it can function according to its intended purpose. Revitalization, as regulated in regulations, seeks to increase the value of the area through development that takes into account local potential, such as history and uniqueness of the location. This research uses a qualitative method based on literature study with in-depth analysis of secondary data from scientific journals, government reports, and revitalization case studies. The aim is to examine strategies for utilizing ex-mining land, especially for food crop farming, which involves the stages of restoration, improvement and maintenance of land function. The research results show that an integrated revitalization and reclamation approach can support ecosystem sustainability while providing economic and social benefits for local communities.